Persepsi Siswa Terhadap Mata Pelajaran Prakarya Dan Kewirausahaan Di Kelas XI MIPA SMA Pembangunan Laboratorium UNP - Melinda Ariska; Asra Ilal Khairi (Journal of Creative Student Research, 2023)
This study aims to find out and describe how students' perceptions of craft and entrepreneurship subjects in class XI MIPA SMA Laboratory Development UNP. This study took 11 (eleven) respondents consisting of representatives of class XI MIPA students. This research method uses a type of qualitative descriptive research. The data collection method uses observation, interview and documentation techniques. The interview technique is conducted unstructured using interview guidelines. Based on the results of the overall research, it was concluded that students' perceptions of craft and entrepreneurship subjects in class XI MIPA were said to be lacking in the teaching techniques used by teachers so, many students felt less interested in craft and entrepreneurship subjects in class XI MIPA SMA UNP Laboratory Development.